Dari Sejarah Menuju Pengembangan Pariwisata Berkelanjutan: Studi Kasus Kampung Wisata Pancer - Irwan Tamrin; Rusdin Tahir; M. Liga Suryadana; Arfah Sahabudin (JURNAL MASTER PARIWISATA, 2021)
Indonesia has made tourism as the leading sector in economy. This has prompted many regions to compete to develop their tourism potential, including Kota Serang - Banten by launching Kampung Wisata Pancer. Kampung Pancer is closely related to the history of the Karangantu Harbour area, which was an international port during the Banten Kingdom era. Not many studies have discussed about the development of sustainable tourism in the Banten region. This article aims to show the progress of tourism in Banten today. Its development has allowed tourism to stand on its own feet. This study is based on an overview of secondary sources and observations and personal interviews with several informants and tourism experts. The results of this study showed that the tourism development efforts in Kampung Wisata Pancer are not in accordance with the concept of sustainable tourism development. Keywords: Tourism Village, Community Based Tourism, Sustainable Tourism Development